Effects of Strength Training on Body Fat in Children and Adolescents with Overweight and Obesity: A Systematic Review with Meta-Analysis - Luis Diego Méndez-Hernández; Esther Ramírez-Moreno; Rosario Barrera-Gálvez; María del Consuelo Cabrera-Morales; Josefina Reynoso-Vázquez; Olga Rocío Flores-Chávez; Lizbeth Morales-Castillejos; Nelly del Socorro Cruz-Cansino; Reyna Cristina Jiménez-Sánchez; José Arias-Rico (MDPI AG, 2022)
Childhood overweight and obesity represent a growing public health problem worldwide. Since the 1980s, the global prevalence of overweight and obesity in childhood and adolescence has increased by 47%. The promotion of exercise is an important intervention to reduce the physical damage of obesity. The meta-analysis was conducted in accordance with the general guidelines for the reporting of systematic reviews and meta-analyses (PRISMA). The PubMed, SciELO, ScienceDirect and Google Scholar databases were searched from August to December 2021. The search yielded 722 titles published between 2000 and 2021. After screening the titles and abstracts, 64 duplicate articles were detected, and 27 articles were ultimately included in the systematic review, including 26 articles published in English and one published in Spanish. There was a statistically significant effect of the strength training interventions on the percentage of body fat, Test of 0 i = (p = 0.00, z = 6.92), Test of 0 = (p = 0.00, Q (9) = 42.63). The findings reveal that strength training has a positive impact on the treatment of body fat in children and adolescents with overweight and obesity.